Enzymatic and Non-Enzymatic Molecules with Antioxidant Function - Paola Irato; Gianfranco Santovito (MDPI AG, 2021)
It is well known that the excessive production of reactive oxygen species (ROS) can lead to the peroxidation of membrane lipids, glycation/oxidation/nitration of proteins, inactivation of enzymes, DNA mutation and damage, and other alterations in the subcellular components [...]